The counter-balance between ammonia absorption and the stimulation of volatilization by periphyton in shallow aquatic systems. (January 2018) - She, Dongli; Wang, Hongde; Yan, Xiaoyuan; Hu, Wei; Zhang, Wenjuan; Li, Jiuyu; Wu, Chenxi; Xia, Yongqiu
Highlights: Two types of SEM methods were evaluated the complex response of NH3 volatilization. N components and pH were the most important factors to NH3 volatilization. Water column exerted greater variation of NH3 loss than sediments and periphyton. Periphyton played trade off effects on NH3 volatilization. Abstract: Ammonia (NH3 ) volatilization is one of the main pathways of nitrogen (N). The aim of this work was to investigate the determinants of NH3 volatilization, and characterize how the overlying water, sediment, and periphyton interact to regulate the rates of NH3 volatilization in shallow aquatic systems. Two types of structural equation modeling (SEM) methods ('elements' and 'components' models) were evaluated to examine the complex multivariate response of NH3 volatilization. The N components and the pH in the 'elements' models exerted significant and positive effects on NH3 volatilization. The water column accounted for the greatest variation of NH3 volatilization in a favorable pH environment and high NH4 + -N concentrations according to the 'components' models. Although periphyton biofilm prohibited the direct flow of NH3 gas, this was counter-balanced by its indirect stimulation effects that positively affected the NH4 + -N and DOC concentrations and the pH in both the overlying water and the sediment.